CURRICULUM MANAGEMENT IN VOCATIONAL EDUCATION: A SYSTEMATIC REVIEW OF DEVELOPMENT, IMPLEMENTATION, INNOVATION, AND QUALITY ASSURANCE (2019–2026) - Muhammad Ariqsyah; Muhammad Akbar; Nizwardi Jalinus; Rijal Abdullah (STKIP Pesisir Selatan, 2026)
Curriculum management is a strategic element in enhancing the relevance of vocational education to the dynamics of industrial development, technology, and labor market needs. However, research on Technical and Vocational Education and Training (TVET) curriculum management remains scattered across various themes and has not yet produced a comprehensive conceptual framework. This study aims to synthesize the development of TVET curriculum management research from 2019 to 2026 and to identify directions for the development of an integrated conceptual framework. The study employed a Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines, analyzing Scopus-indexed articles obtained through Publish or Perish. A total of 400 initial publications were screened based on inclusion and exclusion criteria, resulting in 34 articles that were analyzed using thematic synthesis and bibliometric mapping assisted by VOSviewer. The results show that the publications were dominated by themes such as vocational education, competencies, employability, and pedagogical innovations like Project-Based Learning, Work-Based Learning, and Problem-Based Learning. Conversely, studies on curriculum management, quality assurance, MBKM, Teaching Factory, and accreditation remain fragmented and have not yet been integrated into a single curriculum management model.